Governmental Branding and Food Security: The Role of TNI-AD in Promoting Community Self-Sufficiency - Makmur, Muammar Septian Yuntha; Sari ZA, Lira Retno; Fitrianti, Nabila; Khairunisa, Natashya; Burhan, Syaugi Khairan; Agustini, Prima Mulyasari (Jobmark: Journal of Branding and Marketing Communication, 2026)
Food security has become a pressing global issue, particularly in Indonesia, where it is closely linked to social stability, economic resilience, and political legitimacy. Rising food and energy costs, compounded by climate change, have heightened the urgency of national strategies to secure food availability. This study analyzes the Indonesian National Armed Forces (TNI) food security program through the lens of governmental branding, focusing on how state institutions build trust, loyalty, and public participation by communicating their values and fostering collaboration. Employing a qualitative-descriptive case study approach, the research draws on a literature review and contextual analysis to examine the program's political, sociocultural, and relational dimensions. Politically, the initiative is anchored in legal frameworks and regulations, ensuring legitimacy and accountability. Socioculturally, it reflects the role of community awareness and cultural practices in shaping participation and behavioral change. Relationally, its effectiveness depends on communication strategies and multi-stakeholder collaboration involving farmers, village officials, and community leaders. The findings highlight that food security is not solely a governmental responsibility but also involves the TNI as a strategic actor in safeguarding sovereignty and supporting national development. The study provides evidence that food security in Indonesia requires a collaborative branding strategy that integrates governmental authority, military involvement, and community engagement. In practice, the research offers guidance to policymakers and professionals on designing inclusive strategies that strengthen trust and participation. Academically, it contributes to branding and communication scholarship by framing food security as a governmental branding practice. For society, it underscores the importance of collective responsibility in achieving sustainable food resilience.